Ursane hybrids with 5-amino-1,2,3,4-thiatriazole, 1-tetrazole-5-thione, and 1-tetrazole-5-amines and study of their inhibition of main SARS-CoV-2 protease - Popov, Sergey A.; Shults, Elvira E.; Baev, Dmitry S.; Chirkova, Varvara Yu; Volosnikova, Ekaterina A.; Belenkaya, Svetlana V.; Shcherbakov, Dmitry N.; Pokrovsky, Mikhail.A.; Hamad, Mohammad S.; Pokrovsky, Andrey G. (Steroids, 2025)
•New ursane hybrids with tetrazole and 5-aminothiatriazoles were synthesized.•New compounds were tested in vitro for SARS-CoV-2 3CLpro inhibition.•Hybrids with 1-tetrazol-5-thione inhibited 3CLpro and were non-toxic for Vero cells.•Molecular docking assumed a disulfide bonding between tetrazole-thiol and cysteine of 3CLpro.•The external bonding of triterpenoid is essential for the affinity with the enzyme. A series of new heterocyclic ursane and 28-norursane hybrids − derivatives of 5-amino-1,2,3,4-thiatriazole, 1-tetrazole–5-thione, and 1-tetrazole–5-amines were prepared. Reacting triterpenoids holding NCS groups at different distances from the pentacyclic backbone with hydrazine hydrate resulted in ursane-derived hydrazinecarbothioamides. Subsequent nitrosation afforded terpenoid derivatives of 5-amino-1,2,3,4-thiatriazole. Heterocyclization of amino-thioureas with 3β-acetoxyurs-12-en-28-yl substituent under the action of Hg(OAc)2-NaN3 led to hybrids of 1-tetrazole–5-amines. 1-Tetrazole–5-thiones with different positions of heterocycle relative to the triterpene skeleton were prepared by coupling sodium azide with triterpene isothiocyanates. The activity of the new heterocyclic derivatives as inhibitors of 3CLpro of SARS-CoV-2 was investigated. Remarkable inhibition was observed for the 1-tetrazole-5-thione hybrids of triterpenoids. The highest activity among the studied compounds was provided by the combination of a 1-tetrazole-5-thione moiety at the C(28)H2 group of the ursane frame having a free OH group at the 3-position. Molecular docking assumed the covalent binding of 3CLpro via the formation of a disulfide bond between the thiol groups of the catalytic Cys145 and the tetrazole heterocycle of the new hybrid compounds. The triterpenoid backbone provided multiple external hydrophobic contacts essential for the stability of the complex. The results demonstrate the potential of heterocyclic thione hybrids as non-peptidomimetic covalent inhibitors targeting 3CLpro protease (3-Chymotrypsin-like Protease).